Effect of a Probiotic Supplement Containing Lactobacillus Acidophilus and Bifidobacterium Animalis Lactis on Urine Oxalate in Calcium Stone Formers with Hyperoxaluria: A Randomized, Placebo-controlled, Double-blind and In-vitro Trial - Tavasoli, Sanaz; Jalali, Saba; Naji, Mohammad; Borumandnia, Nasrin; Shakiba Majd, Ghazaleh; Basiri, Abbas; Khosravi Darani, Kianaoush; Karamad, Dina; Tajabadi-Ebrahimi, Maryam; Taheri, Maryam (Urology Journal, 2021)
Purpose: To determine the effect of a probiotic supplement containing native Lactobacillus acidophilus (L. acidophilus) and Bifidobacterium animalis lactis (B. lactis) on 24-hour urine oxalate in recurrent calcium stone formers with hyperoxaluria. Moreover, the in-vitro oxalate degradation capacity and the intestinal colonization of consumed probiotics were evaluated. Materials and Methods: The oxalate degrading activity of L. acidophilus and B. lactis were evaluated in-vitro. The presence of oxalyl-CoA decarboxylase (oxc) gene in the probiotic species was assessed. One hundred patients were randomized to receive the probiotic supplement or placebo for four weeks. The 24-hour urine oxalate and the colonization of consumed probiotics were assessed after weeks four and eight. Results: Although the oxc gene was present in both species, only L. acidophilus had a good oxalate degrading activity, in-vitro. Thirty-four patients from the probiotic and thirty patients from the placebo group finished the study. The urine oxalate changes were not significantly different between groups (57.21 ± 11.71 to 49.44 ± 18.14 mg/day for probiotic, and 56.43 ± 9.89 to 50.47 ± 18.04 mg/day for placebo) (P = .776). The probiotic consumption had no significant effect on urine oxalate, both in univariable (P = .771) and multivariable analyses (P = .490). The consumed probiotics were not detected in the stool samples of most participants. Conclusion: Our results showed that the consumption of a probiotic supplement containing L. acidophilus and B. lactis did not affect urine oxalate. The results may be due to a lack of bacterial colonization in the intestine.